Low‐flow vascular malformations of the hand and forearm: a multidisciplinary experience in a tertiary paediatric centre. Issue 9 (21st January 2021) - Karunaratne, Yasiru G.; Greer, Douglas; Hong, Ling H.; Somia, Naveen; Wargon, Orli; Adams, Susan
Abstract : We present a series of low‐flow vascular malformations of the hand and forearm managed in a tertiary multidisciplinary setting. The complexity of these lesions makes them especially suited to management in this setting. Abstract: Background: Vascular malformations (VMs) involving the hand and forearm in children provide management challenges due to complex anatomy, indispensable functionality and developmental implications. Methods: The institution's Vascular Registry was searched for patients with hand and arm VMs, supplemented by chart review of included patients. Results: Twenty‐one patients were identified, 52% male, with mean presenting age 5.2 years. Venous malformations predominated (71%), followed by lymphatic‐venous (19%), lymphatic (5%) and glomuvenous (5%). Symptoms included pain (76%), swelling (71%), cosmetic concerns (81%), functional compromise (29%) and stiffness (5%). Imaging modality was ultrasound (100%), and magnetic resonance imaging (71%). Treatment included compression (62%), sclerotherapy (62%) and surgery (24%). Post‐sclerotherapy ultrasounds showed complete sclerosis (25%), near complete sclerosis (58%) and partial sclerosis (17%). Post‐surgery, patients reported improved cosmesis (80%), size (100%), pain (60%) and function (40%). Complications occurred in 24%, including bleeding, digital ischaemia and thrombosis. Mean follow‐up was 3.4 years. Conclusion: Children with low‐flow VMs of the hand and forearm experience significant symptoms and functional limitations. A multidisciplinary approach to management ensures optimal outcomes.